The answer is: [A]: " 8m − 3 " .
_________________________________________________
Explanation:
_________________________________________________
(m² + 5m − 7) − (m² − 3m − 4) =
(m² + 5m − 7) − 1(m² − 3m − 4) =
(m² + 5m − 7) − 1m² + 3m + 4) =
m² + 5m − 7 − m² + 3m + 4 ;
________________________________________
Now, combine the "like terms" :
________________________________________
m² − m² = 0 (cancel out).
+5m +3m = +8m ;
− 7 + 4 = -3 ;
________________________________________
And we are left with:
________________________________________
" 8m − 3 " ; which is: Answer choice: [A] .
_______________________________________